Psychotherapy Research: An International Review of Programmatic Studies.
DOI: 10.1037/10092-013
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of divorce and marital distress.

Abstract: Background and Aims HistoryThis program began 15 years ago when Markman, working along with John Gottman and Clifford Notarius at Indiana University, began investigating the causes of marital distress. The initial studies indicated that the quality of couples' communication clearly discriminated between distressed and nondistressed couples. In particular, distressed couples showed a tendency to escalate negatively during discussions of marital issues, whereas nondistressed couples were able to exit the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…These results suggest that the process of change in couple relationships continues beyond the administration of the intervention. This interpretation is consistent with findings from a couple of studies investigating the efficacy of couple psycho-education programs that found initial small or null results shortly postintervention in cases where significant positive outcomes were evident at later follow-up assessments (Markman et al, 1991; Shapiro & Gottman, 2005). This pattern may be even more prevalent than indicated in the literature due to a bias toward not publishing these initial null findings.…”
Section: Communication and The Process Of Therapeutic Changesupporting
confidence: 90%
“…These results suggest that the process of change in couple relationships continues beyond the administration of the intervention. This interpretation is consistent with findings from a couple of studies investigating the efficacy of couple psycho-education programs that found initial small or null results shortly postintervention in cases where significant positive outcomes were evident at later follow-up assessments (Markman et al, 1991; Shapiro & Gottman, 2005). This pattern may be even more prevalent than indicated in the literature due to a bias toward not publishing these initial null findings.…”
Section: Communication and The Process Of Therapeutic Changesupporting
confidence: 90%
“…Several trials show that there is sustained reduction in negative communication after skills‐based relationship education (Halford et al). Furthermore, two quasi‐experimental studies (Hahlweg, Markman, Thurmaier, Engl, & Eckert, 1998; Markman, Floyd, Stanley, & Storaasli, 1988) and one randomized controlled trial (Halford, Sanders, & Behrens, 2001) found that skills‐based relationship education helps couples maintain relationship satisfaction across the early years of first marriages. However, in the Halford et al (2001) trial, the benefits of skill‐based relationship education were restricted to couples defined as high risk for future marital problems, and high risk was operationalized as the woman's parents having been divorced or the man's parents having been aggressive.…”
Section: Negative and Withdrawing Communication And Relationship Educmentioning
confidence: 99%
“…The term skill training has been used in the research literature to describe approaches that focus on active training of skills, though these approaches typically include other components (e.g., building awareness and cognitive change; Stanley, 2001). Examples of skill‐training programs include the Relationship Enhancement program (RE; Guerney, 1987), the Premarital Relationship Enhancement Program (PREP; Markman, Floyd, Stanley, & Storaalsi, 1988), and the Couples Communication Program (CCP; Miller, Miller, Nunnally, & Wackman, 1992). These various skill‐training programs have a number of content areas in common.…”
Section: Approaches To Relationship Educationmentioning
confidence: 99%
“…Significant variations also exist. For example, in PREP, there are multiple foci of intervention, but the most time is devoted to prevention of destructive conflict because this is argued to be central to the prevention of relationship problems (Markman et al, 1988). In contrast, in RE, the development of partner empathy receives very strong emphasis (Guerney, 1987).…”
Section: Approaches To Relationship Educationmentioning
confidence: 99%